Pengembangan Aplikasi Pengelolaan E-Archive dengan Fitur Tracking Perubahan Dokumen Berbasis Appsheet di PT X - Devina Dyah Puspita Sari; Susan Febriantina; Bayu Suhendry (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Digital archive management plays an important role in supporting administrative effectiveness. However, the archive management process in the Operations Management Support Division of PT X still faces challenges, particularly the absence of a system to monitor document progress and automatically record document modification history. This study aims to develop an AppSheet-based digital archive management application, implement a Document Change Tracking feature, and evaluate the application's feasibility. This study employed the Research and Development (R&D) method using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The application was developed using AppSheet integrated with Google Sheets and evaluated through Black Box Testing, expert validation, and user testing. The results show that the application was successfully developed with document management, categorization, progress monitoring, email notification, and Document Change Tracking features that automatically record document modification activities through a ChangeLog. All application functions operated properly. The media expert, subject matter expert, and user evaluations obtained feasibility scores of 89.09%, 95.56%, and 95.33%, respectively, all categorized as Highly Feasible. Therefore, the application is considered suitable for supporting digital archive management at PT X.